P51 Comorbidities and the clinical pathway to access joint replacement surgery: an exploratory qualitative study. (September 2018) - Podmore, B; Hutchings, A; Durand, MA; Robson, J; Konan, S; van der Meulen, J; Lynch, R
Abstract : Background: Hip and knee replacement surgery is one of the most common and effective surgical procedures. The rise in multi-morbidity world-wide is leading to increasing numbers of patients with comorbid conditions undergoing joint replacement surgery. Financially stretched commissioners of health care services in the English National Health Service (NHS) are increasingly seeking to restrict access to elective surgery, including hip and knee replacement surgery despite a lack of evidence to support these decisions. It is important to get a better understanding of the referral and selection of patients with comorbidities for joint replacement surgery. Methods: An exploratory qualitative approach involving semi-structured interviews with eight orthopaedic surgeons, seven general practitioners (GPs), and five professionals working in intermediate musculoskeletal services (specific centres within the English NHS to support the referral process from primary to specialised care). Results: In general, the presence of comorbidities was not seen as a barrier to being referred or selected for joint replacement. Each professional group, however, concentrated on different aspects of the patients' condition which appeared to affect how each group managed patients with comorbidities. GPs focused on the long-term impact that comorbidities have on the patients' everyday life. Intermediate care professionals focused on the short-term impact of comorbidities on the patients' likelihood of being selected for surgery. Orthopaedic surgeons focused on the short-term impact of comorbidities on the surgery itself. This implied there was a disagreement about roles and responsibilities in the management of patients with comorbidities. None of the three groups believed it was their responsibility to address comorbidities in preparation for surgery. This disagreement was identified as a reason why some patients seem to 'get lost' in the referral system when they were considered to be unprepared for surgery. Patients were then potentially left to manage their own comorbidities before being reconsidered for joint replacement. Conclusion: At the clinician-level, comorbidities were not perceived as a barrier to accessing joint replacement surgery but at the pathway-level, it may create an implicit barrier such that patients with comorbidities may get 'lost' to the system. The current orthopaedic clinical pathway may be less suitable for patients with comorbidities.